Revisiting metastatic central nervous system tumors with unknown primary using clinicopathological findings: A single neurosciences institutional study - Anshu Gupta; Sujata Chaturvedi; Deepak Jha; Monali Chaturvedi (Wolters Kluwer Medknow Publications, 2019)
Background: Metastatic tumors are the most common central nervous system (CNS) tumors wherein the primary site remains unknown in most of the cases. Aim: The study was carried out to evaluate metastatic CNS tumors with unknown primary by using simplified diagnostic (clinico-histopathologic) approach. Material and Methods: A 2 years study was conducted on 32 cases of CNS metastases having unknown primary tumors in a neurosciences institute. Statistical Analysis: All the results were prepared using software version of SPSS 22. Results: The most common metastatic site found in brain was cerebrum (59.3%) [frontal > frontoparietal > parieto-occipital > temporal] [left cerebrum > right cerebrum], followed by cerebellum (12.5%), spinal cord (9.3%), and leptomeninges (3.12%). Most of the metastatic tumors presented as ill-defined (34%) rather than well-defined (22%) lesions with ring enhancement seen only in 16% of the cases on magnetic resonance imaging (MRI).On histopathology findings with targeted immunohistochemistry, most common histological tumor type identified irrespective of site was adenocarcinoma (68.7%), followed by squamous cell carcinoma (15.6%) and poorly differentiated carcinoma (12.5%). Only one case of lymphoma was reported. Corroborating all the above findings along with clinical history and other relevant investigations, primary sites could be detected in 23 cases (71.8%).The most common primary site deduced was lungs (39.1%), followed by thyroid (17.3%), breast in females (13.0%), gastrointestinal tract (8.6%), and prostate in males (4.3%). Only in nine cases (28.1%) with mainly poorly differentiated histopathological type, primary site remained unknown. Conclusion: Detection of the primary site in metastatic CNS tumors is possible by adopting this simple and effective diagnostic approach at centers/hospitals having cost and other constraints.